Multidisciplinary relationship between periodontology and orthodontic department: a clinical audit study / Nurul Saadah Razali, Fara Azwin Adam and Erni Noor - Razali, Nurul Saadah; Adam, Fara Azwin; Noor, Erni (Faculty of Dentistry, Universiti Teknologi MARA, 2024)
Objectives: This study aims to assess the current practice among postgraduate students in the multidisciplinary interaction between the Periodontology and Orthodontic Departments in the Faculty of Dentistry, UiTM Sungai Buloh; we conducted clinical audit research. Material and methods: Data retrieval from the Integrated Dental Record Management System (iDeRMS) was used to conduct our clinical audit. Results: After receiving orthodontic treatment, 25% of the referral cases, according to our study, needed non-surgical periodontal therapy. Additionally, we discovered that 16.7% of patients required surgical periodontal treatment after being sent for orthodontic care. Conclusion: A multidisciplinary approach might be necessary to successfully treat periodontal disease. As periodontal therapy is a requirement for the success of orthodontic treatment, and orthodontic treatment contributes to preserving periodontal health, a reciprocal link between the two specialities is essential.